2001
DOI: 10.1590/s0100-879x2001000800009
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of a monoclonal antibody against an Ascaris suum allergenic component

Abstract: Ascaris suum allergenic components (PIII) separated by gel filtration chromatography of an adult worm extract were used to immunize BALB/c mice. Popliteal lymph node cells taken from the immunized animals were fused with SP2/O myeloma cells using polyethylene glycol (MW 1450) as fusogen. The hybridomas were cultured in HATcontaining medium and cloned at limiting dilutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Moreover, we also showed that the immunosuppressive and allergenic effects are due to distinct components of A. suum adult worms [7]. While the 29 kDa components induce IgE antibody production (8), the high molecular mass components, like the whole extract, display suppressive effects on the Th1 and Th2 immune responses to unrelated antigens (9). More recently, we isolated from Ascaris suum extract a single protein (PAS-1) that is responsible for the suppressive activity of the whole extract on humoral immune response [10].…”
Section: Introductionmentioning
confidence: 62%
“…Moreover, we also showed that the immunosuppressive and allergenic effects are due to distinct components of A. suum adult worms [7]. While the 29 kDa components induce IgE antibody production (8), the high molecular mass components, like the whole extract, display suppressive effects on the Th1 and Th2 immune responses to unrelated antigens (9). More recently, we isolated from Ascaris suum extract a single protein (PAS-1) that is responsible for the suppressive activity of the whole extract on humoral immune response [10].…”
Section: Introductionmentioning
confidence: 62%
“…In particular, significant effects of PAS-1 have been demonstrated in allergy. Itami et al [67] used a murine model of asthma induced by another A. suum -molecule, APAS-3 that promotes IgE production [181], to test the suppressive effect of PAS-1 [182]. In this experimental model of asthma induced by APAS-3, PAS-1-treated mice showed decreased eosinophil migration into the lungs, lower IL-4, IL-5, CCL11 and RANTES production in the BAL, as well as reduced airway hyperreactivity.…”
Section: Immunomodulatory Effects Of Helminth-derived Molecules Anmentioning
confidence: 99%
“…We have also demonstrated that the immunosuppressive and stimulatory effects are due to distinct components of A. suum adult worms (8). While the high molecular mass components strongly suppress the humoral and cellular immune responses (9), the 29-kDa components induce IgE antibody production (10). In the present study we produced specific monoclonal antibodies against A. suum immunosuppressive components, which can be important tools for the identification and further characterization of these proteins.…”
mentioning
confidence: 90%